REPRESENTASI KONFLIK KEBANGKITAN SOSIAL DALAM FILM ANIME ONE PIECE ARC DRESSROSA (STUDI ANALISIS ROLAND BARTHES) - M. Soffan Azis; Nurma Yuwita (CV SWA ANUGERAH, 2023)
Name M. Soffan Azis, Communication Studies Program at Yudharta University Pasuruan 2023. Representation of Social Development Conflicts in the Anime One Piece Arc Dressrosa, Supervisor Nurma Yuwita, S., M.I.Kom. Movies have appeal for children to adults. The One Piece Anime film was produced in 1999 and is now available in the Bstation application. His goal is to find the world's greatest treasure, known as